The Syntactic Deletion in the Poetry of Al-Raai Al-Namiri - Qasim Hassan , Riyadh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Deletion is both a rhetorical and grammatical device in which one of the elements of a sentence is omitted while the meaning remains intelligible through its context. It is, in essence, one of the distinctive features of the Arabic language, employed to achieve artistic expression, brevity, and eloquence. Through deletion, the writer allows space for the reader’s reflection, thereby transforming it into a linguistic art that demonstrates the author’s ability to convey meaning in the most concise and powerful form. Deletion is among the significant aspects that enhance communication and enrich linguistic performance, serving various purposes such as alleviating redundancy and avoiding repetition, thus making it a standardized tool accessible to linguists. This study is limited to examining this phenomenon, which contributes to the aesthetic and semantic richness of literary texts, particularly in the poetry of Al-Raai Al-Namiri. His poetry reveals multiple manifestations of deletion and diverse purposes behind its use, making it a phenomenon worthy of in-depth analysis and focused study. DOI: https://doi.org/10.54633/2333-024-056-020